Designing a Low Frequency Delay Line - Shkvarnitskaya, Tatiana; Kataieva Мariia; Kvasnikov, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
Expressions were obtained for the phase characteristic of the delay line with active losses. Linearity of the phase characteristic is estimated. The experimental results are presented.